Sexually Transmitted Infections in Association With Area-Level Prostitution and Drug-Related Arrests. Issue 7 (July 2021) - Magee, Lauren A.; Fortenberry, James Dennis; Nelson, Tammie; Roth, Alexis; Arno, Janet; Wiehe, Sarah E.
Abstract : Objectives: This study aimed to examine the mediators and moderators of area-level prostitution arrests and sexually transmitted infections (STIs) using population-level data. Methods: Using justice and public health STI/HIV data in Marion County (Indianapolis), Indiana, during an 18-year period, we assessed the overall association of area-level prostitution and drug-related arrests and STI/HIV, and mediators and moderators of the relationship. Point-level arrests were geocoded and aggregated by a census block group. Results: Results indicate a positive relationship between numbers of prostitution arrests and area-level STI rates. There was a dose-response relationship between prostitution arrests and STI rates when accounting for drug-related arrests. The highest quintile block groups had significantly higher rates of reported chlamydia (incident rate ratio [IRR], 3.29; 95% confidence interval [CI], 2.82–3.84), gonorrhea (IRR, 4.73; 95% CI, 3.90–5.57), syphilis (IRR, 4.28; 95% CI, 3.47–5.29), and HIV (IRR, 2.76; 95% CI, 2.24–3.39) compared with the lowest quintile. When including drug arrests, the second (IRR, 1.19; 95% CI, 1.03–1.38) and the third (IRR, 1.20; 95% CI, 1.02–1.41) highest quintile block groups had lower IRR for reported rates of chlamydia, indicating that drug arrests mediated the prostitution arrest effect. Conclusions: These findings inform public health agencies and community-based organizations that conduct outreach in these areas to expand their efforts to include harm reduction and HIV/STI testing for both sex workers and individuals experiencing substance use disorder. Another implication of these data is the importance of greater collaboration in public health and policing efforts to address overlapping epidemics that engage both health and legal interventions. Abstract : Our study demonstrates the overlapping but distinctive ways by which communities are differentially represented in sexually transmitted infection surveillance data: both prostitution arrests and drug-related arrests are associated with area-level sexually transmitted infection rates.Supplemental digital content is available in the text.